Semaphorin 3A Induces Odontoblastic Phenotype in Dental Pulp Stem Cells. (October 2016) - Yoshida, S.; Wada, N.; Hasegawa, D.; Miyaji, H.; Mitarai, H.; Tomokiyo, A.; Hamano, S.; Maeda, H.
In cases of pulp exposure due to deep dental caries or severe traumatic injuries, existing pulp-capping materials have a limited ability to reconstruct dentin-pulp complexes and can result in pulpectomy because of their low potentials to accelerate dental pulp cell activities, such as migration, proliferation, and differentiation. Therefore, the development of more effective therapeutic agents has been anticipated for direct pulp capping. Dental pulp tissues are enriched with dental pulp stem cells (DPSCs). Here, the authors investigated the effects of semaphorin 3A (Sema3A) on various functions of human DPSCs in vitro and reparative dentin formation in vivo in a rat dental pulp exposure model. Immunofluorescence staining revealed expression of Sema3A and its receptor Nrp1 (neuropilin 1) in rat dental pulp tissue and human DPSC clones. Sema3A induced cell migration, chemotaxis, proliferation, and odontoblastic differentiation of DPSC clones. In addition, Sema3A treatment of DPSC clones increased β-catenin nuclear accumulation, upregulated expression of the FARP2 gene (FERM, RhoGEF, and pleckstrin domain protein 2), and activated Rac1 in DPSC clones. Furthermore, in the rat dental pulp exposure model, Sema3A promoted reparative dentin formation with dentin tubules and a well-aligned odontoblast-like cell layer at the dental pulp exposure site and with novel reparative dentin almost completely covering pulp tissue at 4 wk after direct pulp capping. These findings suggest that Sema3A could play an important role in dentin regeneration via canonical Wnt/β-catenin signaling. Sema3A might be an alternative agent for direct pulp capping, which requires further study.